A Bioinspired, Reusable, Paper‐Based System for High‐Performance Large‐Scale Evaporation. (23rd March 2015) - Liu, Yanming; Yu, Shengtao; Feng, Rui; Bernard, Antoine; Liu, Yang; Zhang, Yao; Duan, Haoze; Shang, Wen; Tao, Peng; Song, Chengyi; Deng, Tao
<x xml:space="preserve">Abstract</x> A bioinspired, reusable, paper‐based gold‐nanoparticle film is fabricated by depositing an as‐prepared gold‐nanoparticle thin film on airlaid paper. This paper‐based system with enhanced surface roughness and low thermal conductivity exhibits increased efficiency of evaporation, scale‐up potential, and proven reusability. It is also demonstrated to be potentially useful in seawater desalination.